Delayed effects on migration intentions in an information provision experiment in Ghana - Sarah Frohnweiler; Bernd Beber; Cara Ebert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We report experimental results from Ghana, where treated subjects received information on regional income differentials. We do not see an effect on migration intentions directly after the intervention, but the effect of the treatment unfolds over time. Eighteen months later, subjects assigned to receive income information are on average significantly less likely to express enthusiasm for moving to another region, because individuals that had inaccurately high expectations about incomes elsewhere compared to their current place of residence are now more likely to want to forgo relocation. Contrary to common claims that effects observed in light-touch information experiments are likely to dissipate quickly, we suggest that some types of content in high-stakes domains such as migration can take time to reverberate and be incorporated into individuals' decision calculus. We also discuss that delayed effects may be uncommonly observed because long-term follow-ups are rare in the absence of short-term effects. – – Wir berichten Ergebnisse eines Experiments in Ghana, bei dem behandelte Personen Informationen über regionale Einkommensunterschiede erhielten. Unmittelbar nach der Intervention lässt sich keine Auswirkung auf Migrationsabsichten feststellen, aber eine Wirkung entfaltet sich im Laufe der Zeit. Achtzehn Monate später ist die Wahrscheinlichkeit, dass die Teilnehmenden, die Informationen über Einkommensunterschiede erhalten haben, in eine andere Region umziehen wollen im Durchschnitt deutlich geringer. Dies liegt daran, dass Personen, die im Vergleich zu ihrem derzeitigen Wohnort unzutreffend hohe Einkommenserwartungen hatten, nun eher auf einen Umzug verzichten wollen. Entgegen der weit verbreiteten Annahme, dass sich Effekte in Experimenten dieser Art schnell verflüchtigen, zeigen wir, dass Inhalte in Themenfeldern wie der Migration eventuell eine gewisse Zeit brauchen, bis sie nachhallen und in das Entscheidungskalkül der Menschen einfließen. Wir erörtern auch, dass verzögerte Effekte nur selten beobachtet werden, weil langfristige Folgeuntersuchungen selten sind, wenn es keine kurzfristigen Effekte gibt.
Keywords: J31; O15; 330; Delayed effects; information provision; migration intentions